Pengaruh Karakteristik Pemerintah Daerah dan Hasil Pemeriksaan Audit BPK Terhadap Kinerja Keuangan - Annas L Mappiasse (Bongaya Journal of Research in Accounting (BJRA), 2018)
This research is related to the issue performance of local government in Indonesia, which needs to beimproved after the introduction of regional autonomy. Each of local governments need to establish and manage their own public financial management system. Many factors may affect the financial performance of local government. This study aimed to examine whether the characteristics of the local governments and the results of the audit can improve the financial performance of local government, as measured by the efficiency ratio. By using multiple regression analysis on 94 samples of local government financial report for year 2011, the study was able to prove that the dependence level and government expenditures have positive significant effect on financial performance. Legislative and the audit findings have negative significant effect on financial performance. While the size, wealth, and audit opinions do not affect the financial performance of thegovernment in the island of Java.